The Role of Creative Self-Concept in Mediating the Effects of Critical Openness and Reflective Skepticism on Cooperative Mindset - Winda Hayu Pangesti; Ida Nur Aeni (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study examined how reflective skepticism and critical openness affect cooperative attitudes by mediating creative self-concepts. The basis of this research is the importance of fostering a collaborative mindset in higher education, which can encourage teamwork, creativity, and innovative problem-solving. This study uses a quantitative, survey-based approach. The population in this study comprises active students in the economic education study program, totaling 417 students. The sampling technique uses probability sampling, specifically simple random sampling, meaning students are selected at random without specific qualifications. The sample size was determined using the Slovin formula, resulting in 204 students. These findings suggest that reflective skepticism and critical openness positively and significantly affect cooperative mindsets. Furthermore, it was shown that the influence of cooperative mindset and critical openness is mediated by creative self-concept. However, similar mediation was not found in the influence between reflective skepticism and cooperative mindsets. The study concluded that, in a collaborative learning setting in higher education, fostering a cooperative mentality requires the development of critical thinking skills and a creative self-concept.